Tromboembolismo venoso - Veiga, Alessandro Gabriel M.; Santos, Izolete Aparecida T. [UNESP]; Passeri, Celso Roberto; Papini, Silvia Justina [UNESP] (My University, 2013)
Venous thromboembolism (VTE) is a severe disease with high incidence worldwide, and, if it is not diagnosed early and properly treated, VTE can evolve and cause serious complications such as deep vein thrombosis (DVT) and pulmonary embolism (PE). In cancer patients these diseases are responsible for high morbidity and mortality rates. Clinical presentation is varied and the early diagnosis and treatment depend on high clinical suspicion and appropriate workup. This review will describe to VTE and its effects in cancer patients. © Copyright Moreira Jr. Editora.Todos os direitos reservados.
Venous thromboembolism